2014
DOI: 10.1037/a0035643
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in veterans health administration mental health providers in posttraumatic stress clinics.

Abstract: The purpose of this study was to conduct the first assessment of burnout among Veterans Health Administration (VHA) mental health clinicians providing evidence-based posttraumatic stress disorder (PTSD) care. This study consisted of 138 participants and the sample was mostly female (67%), Caucasian (non-Hispanic; 81%), and married (70%) with a mean age of 44.3 years (SD = 11.2). Recruitment was directed through VHA PTSD Clinical Teams (PCT) throughout the United States based on a nationwide mailing list of PCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…Although staffing is costly, increased delivery of EBPs may well result in long-term reductions in veterans’ service and disability needs, making staffing investments likely to prove cost-effective over time. The association between having emotional support from co-workers and increased adherence to the PE manual also suggests that maintaining high-quality relationships among PCT providers may have relevance not only for staff well-being (Garcia, McGeary, McGeary, Finley, & Peterson, 2014), but for the quality of care provided. Foa, Hembree, & Rothbaum (2007) have recommended that PE providers discuss challenging cases or seek emotional support when necessary, and dedicating time for VA mental health providers to engage in these activities may help to promote more effective delivery of evidence-based care.…”
Section: Discussionmentioning
confidence: 99%
“…Although staffing is costly, increased delivery of EBPs may well result in long-term reductions in veterans’ service and disability needs, making staffing investments likely to prove cost-effective over time. The association between having emotional support from co-workers and increased adherence to the PE manual also suggests that maintaining high-quality relationships among PCT providers may have relevance not only for staff well-being (Garcia, McGeary, McGeary, Finley, & Peterson, 2014), but for the quality of care provided. Foa, Hembree, & Rothbaum (2007) have recommended that PE providers discuss challenging cases or seek emotional support when necessary, and dedicating time for VA mental health providers to engage in these activities may help to promote more effective delivery of evidence-based care.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested that certain aspects of the VHA workplace may serve to inoculate against burnout, such as better pay, more job security, and focus on quality improvement (Salyers, Rollins, Kelly, Lysaker, & Williams, ). In an examination of burnout among PCT clinicians, Garcia, McGeary, McGeary, Finley, and Peterson () found that workplace factors predicted burnout but that demographic characteristics did not. Specifically, the researchers found that PCT providers who felt they lacked control over their work, or that they had too much clinical work, reported greater exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout may occur when providers experience exhaustion, cynicism, and inefficacy in the face of chronic emotional and interpersonal stressors at work (Maslach, Schaufeli & Leiter, 2001). Recent research has examined how organizational factors impact burnout, and findings indicate that high caseloads may contribute to the exhaustion of providers (that is, PTSD Clinical teams [PCT]) in the Veterans Health Administration (VHA; Garcia, McGeary, McGeary, Finley, & Peterson, 2014;McGeary et al, 2016). Garcia and colleagues (2014) social costs to these clinicians burning out and thus recommend supporting VHA infrastructure to guard against burnout.…”
Section: The Issue Of Provider Burnoutmentioning
confidence: 99%